PENGEMBANGAN LITERASI BUDAYA MELALUI SENI TARI TRADISIONAL PADA PEMBELAJARAN SBDP DI SDN PALEBON 01 SEMARANG - Helga Nur Pridyawati; Mei Fita Asri Untari; Rofian (STKIP Subang, 2025)
This research is motivated by the lack of cultural literacy through traditional dance in SBdP (Art, Culture, and Craft) learning at SDN Palebon 01 Semarang. The focus of this study is to explore how cultural literacy, particularly in traditional dance, is implemented in SBdP lessons at SDN Palebon 01 Semarang. The objective of this research is to find out how traditional dance is taught in SBdP subjects in Grade 5 at SDN Palebon 01 Semarang. This study uses a qualitative research approach with a descriptive method. The research was conducted at SDN Palebon 01 Semarang. Data collection methods included observation, interviews, and documentation. The results showed that cultural literacy through traditional dance in SBdP learning is still lacking. Students are unable to understand traditional dance lessons in depth. They do not receive projects or assessments related to traditional dance in SBdP, resulting in students only recognizing the names of traditional dances and their regions of origin. This condition is mainly due to the teacher rarely teaching traditional dance, which stems from a lack of interest or competence in the subject. Based on these findings, the suggested recommendation is: if a teacher feels less competent in teaching dance, it would be beneficial for them to study dance through books or other available resources. In addition, teachers are encouraged to develop well-structured learning media and tools to support their delivery of the material in class. This will enable teachers to conduct assessments through traditional dance activities in SBdP lessons for Grade 5 students at SDN Palebon 01 Semarang.